Comparable Worth Exercise - Aldrich, H. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Two jobs: Cashier at Lenoir versus Subway sandwich shop manager at Lenoir.Decide what the scale definitions should be, from 0 to 5, and how much they should count in the overall job evaluation – that’s the "weight." Then, for each job, give it a scale value from 0 to 5, based on your definition.